THE EFFECT OF OWNERSHIP STRUCTURE ON FINANCIAL DISTRESS: EVIDENCE IN INDONESIAN MANUFACTURING COMPANIES - Lintang Santoso; Yeterina Widi Nugrahanti (JRAK, 2022)
This study aims to determine the effect of ownership structure on financial distress. The research method used in this study is quantitative methods and data collection techniques using purposive sampling. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. This research uses the panel data regression analysis technique. From testing the estimation model, it was found that the Fixed Effect Model was the chosen estimator. The classic assumption test is problematic, so the mode is changed to the GLS panel. The results of this study are Managerial Ownership, Institutional Ownership, and Foreign Ownership and have a negative influence on financial distress. The government Ownership variable does not affect financial distress.